1998
DOI: 10.1598/rrq.33.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dyslexia From Kindergarten: The Importance of Distinctness of Phonological Representations of Lexical Items

Abstract: S This article presents results from a longitudinal study of children of dyslexic and of normally reading parents. The children were followed from the beginning of kindergarten (at the age of 6, 1 year before reading instruction in Denmark) until the beginning of the second grade. Children of dyslexic parents were found to have an increased risk of dyslexia (a 4.3 odds ratio) when dyslexia was defined as poor phonological recoding (poor reading of nonwords and pseudohomophones of real words). All language meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
404
7
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(481 citation statements)
references
References 69 publications
(72 reference statements)
56
404
7
14
Order By: Relevance
“…More important, because of the nature of how listeners represent and process coarticulation, poorer performance by dyslexics on this task implies that their phonological representations for common words are less well integrated than those of normally achieving readers. This finding extends previous results obtained with gating tasks in dyslexic samples (Boada & Pennington, 2006;Griffiths & Snowling, 2001;Metsala, 1997b) and supports the growing literature suggesting that dyslexics have less complete phonological representations of printed words (Elbro et al, 1998;Swan & Goswami, 1997;Wesseling & Reitsma, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More important, because of the nature of how listeners represent and process coarticulation, poorer performance by dyslexics on this task implies that their phonological representations for common words are less well integrated than those of normally achieving readers. This finding extends previous results obtained with gating tasks in dyslexic samples (Boada & Pennington, 2006;Griffiths & Snowling, 2001;Metsala, 1997b) and supports the growing literature suggesting that dyslexics have less complete phonological representations of printed words (Elbro et al, 1998;Swan & Goswami, 1997;Wesseling & Reitsma, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…A problem with this approach is that phonological awareness at the level of the phoneme appears not to develop actively until the onset of reading instruction, and it may be heavily influenced by the individual's experience with printed words in alphabetic languages (Morais, Cary, Alegria, & Bertelson, 1979;Perfetti, Beck, Bell, & Hughes, 1987;Ziegler & Goswami, 2005). Others have argued that poor performance on phonological awareness tasks may reflect incomplete or inaccurate phonological representations rather than analytic problems per se (Boada & Pennington, 2006;Elbro, Borstrom, & Petersen, 1998;Fowler, 1991;Snowling & Hulme, 1989;Swan & Goswami, 1997). We term this broad view the phonological representations hypothesis (after Swan & Goswami, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In yet other studies, facility at recognising spoken words from sparse neighbourhoods emerged as a predictor (Garlock et al, 2001;Metsala et al, 2009). Although this latter finding does not appear consistent with LR predictions, it could be that this measure acts as an index of the quality of the underlying speech representations that may underpin both vocabulary acquisition and phonological awareness (e.g., Boada & Pennington, 2006;Elbro et al, 1998). …”
Section: Influence Of Vocabulary Growthmentioning
confidence: 71%
“…While receptive vocabulary is a strong correlate of phonological awareness in some studies (McBride-Chang, Wagner, & Chang, 1997;Metsala, 1999), others have failed to find such a relationship (Elbro, Borstrom, & Petersen, 1998;Garlock, Walley, & Metsala, 2001). In yet other studies, facility at recognising spoken words from sparse neighbourhoods emerged as a predictor (Garlock et al, 2001;Metsala et al, 2009).…”
Section: Influence Of Vocabulary Growthmentioning
confidence: 95%
“…Parents of children with language difficulties may also adjust their linguistic input during home literacy activities in line with their children’s productive skills (Majorano & Lavelli, 2014). In contrast, studies to date have reported minimal differences in the frequency and quality of literacy activities provided by parents who are dyslexic readers in comparison with typical readers (Elbro, Borstrøm, & Petersen, 1998; Laakso, Poikkeus, & Lyytinen, 1999; Van Bergen, Jong, Plakas, Maassen, & Leij, 2011), and the limited literature has not taken into account the reading skills of parents themselves.…”
mentioning
confidence: 99%